2013
DOI: 10.1007/s13142-013-0245-9
|View full text |Cite
|
Sign up to set email alerts
|

The Affordable Care Act and implications for young adult health

Abstract: In the USA, young adults are most likely to be uninsured and least likely to report a usual source of medical care than any age group. The Patient Protection and Affordable Care Act (ACA) recognizes the critical need for expanded insurance coverage for this age group, and multiple provisions of the ACA address insurance coverage and health care utilization in young adults. This paper presents a brief overview of the challenges of maintaining health insurance coverage and accessing health care in young adults, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Young women are less likely to want a pregnancy at this stage in their lives [3], and may have less access to reproductive health care than their older counterparts [7]. At the same time, women in the South have less access to the full spectrum of reproductive health services than women in other parts of the country [8].…”
Section: Introductionmentioning
confidence: 99%
“…Young women are less likely to want a pregnancy at this stage in their lives [3], and may have less access to reproductive health care than their older counterparts [7]. At the same time, women in the South have less access to the full spectrum of reproductive health services than women in other parts of the country [8].…”
Section: Introductionmentioning
confidence: 99%
“…26 Predictions of how subsequent provisions, including expansion of Medicaid eligibility to 133% of the federal poverty level, introduction of state health insurance exchanges, and provision of income-based tax subsidies, could affect trauma patients and the viability of trauma hospitals are contentiously mixed. [27][28][29][30][31][32] The objective of this study was to assess for observed changes in insurance coverage and rehabilitation use among young adult trauma patients associated with the ACA, including introduction of the DCP and Medicaid expansion/open enrollment. We considered possible differences between DCPeligible vs -ineligible patients and among stratified demographic and community subgroups.…”
mentioning
confidence: 99%
“… 29 In the United States, the Patient Protection and Affordable Care Act (ACA) since 2010 enables young adults to remain as dependents on their parents’ health insurance until age 26 and expands insurance coverage including mandatory coverage for preventive services with no copayment. 4 , 5 , 30 Many studies reported that the ACA provision significantly improved young adults’ access to and utilization of healthcare services and provided protection against overall out-of-pocket medical expenditures. 9 , 27 , 30 32 …”
Section: Discussionmentioning
confidence: 99%